2014
DOI: 10.2105/ajph.2014.302139
|View full text |Cite
|
Sign up to set email alerts
|

Dentist Supply and Children’s Oral Health in the United States

Abstract: Dentist supply is associated with improved oral health for younger children in urban settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…These results are consistent with previous studies reporting a positive association between dentist supply and use of preventive dental care using state‐level data (e.g., Lin et al. ), and that such association becomes less prominent after adjusting for additional state‐level characteristics (Guarnizo‐Herreno and Wehby ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous studies reporting a positive association between dentist supply and use of preventive dental care using state‐level data (e.g., Lin et al. ), and that such association becomes less prominent after adjusting for additional state‐level characteristics (Guarnizo‐Herreno and Wehby ).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Guarnizo‐Herreno and Wehby () investigated the relationship between supply of dentists and children's oral health at the national level and found that living in an area with more dentists improved oral health outcomes among children. Chi and Leroux () reviewed county‐level determinants of dental utilization for children with chronic conditions in Iowa and found that professional shortage areas predict a lower likelihood of child dental care.…”
mentioning
confidence: 99%
“…16,17 In regions of the United States, as well, the concentration of dentists varies, from highest rates in Northeast to lowest in the South. 18 The majority of work on geographic variability has focused on urban-rural differences in oral health workforce, 18,19 access, 20-24 and oral health status. 23 Recently, the Pew Center on the States published a comparison of state dental policies for children, which showed broad variation by state and a sobering two-thirds of states that are not adequately providing for basic dental care for children.…”
mentioning
confidence: 99%
“…The greater percentage of dentists reporting paediatric extractions in FH clinics reflects the absence of paediatric dentists. Workforce qualification and availability have a direct effect on oral health (21,22). Endodontic treatment was reported to be provided by more FH than MCH dentists with wider gap in multi-root teeth.…”
Section: Discussionmentioning
confidence: 99%